School-Based Health Education Research: Charting the Course for the Future. Issue 1 (2nd January 2021) - Benes, Sarah; Boyd, Kelly M.; Cucina, Irene; Alperin, Holly L.
ABSTRACT: SHAPE America has identified four goals as part of the 50 Million Strong by 2029 initiative; one of these goals is healthy behavior. School-based health education is uniquely positioned to be a primary route through which this goal can be achieved. Health education is an academic subject included in a well-rounded education, based on health behavior and learning theory, research-based and taught by licensed and trained health educators with adequate instructional time. Health education helps students acquire functional knowledge about a variety of topics and develop health-related skills resulting in personal competence and self-efficacy. The purpose of this paper is to provide an overview of the existing evidence examining school-based health education and to articulate future directions for research that will solidify school-based health education as a necessary and efficacious strategy for improving the health and wellness of youth.